(untitled) (European Journal of Health Research, 2019)
Nowadays, a demographic shift is taking place in the environment of older people. There are more and more people of advanced age and diverse states of health. The profesional carers are one of the indirect protagonists of this demographic shift and the burnout is one of the main stressors faced by professional carers. Burnout is a psychological syndrome consisting of professional exhaustion and, despite of the fact that it has been studied by numerous authors, there is no single conceptualization. Therefore, the following question arises: How does the burnout level affect the health of formal carers? The selected subjects belong to an elderly home in the Community of Madrid. Two previously validated questionnaires on health (SF-36) and Burnout (Maslach Burnout Inventory) were filled and the analysis was carried out through the statistical programme SPSS15. A low level of burnout is observed in the workers and a high level of health. The correlations between both questionnaires are not statistically significant, which does not follow the results found by other researchers. These results give us positive conclusions regarding to the workers of the center, who are in a high standard of health.